Leadership in disaster management: theory versus reality - Mahmud, Aidalina; Mohammad, Zaahirah; Abdullah, Khairul Anuar (Faculty of Medicine, Universiti Teknologi Mara, 2020)
Leaders should be competent in managing disaster situations to minimize the damage of the events. However, when disaster strikes these leadership competencies may not always come into play. This paper aims to identify the incongruence between what leaders should do and what leaders do when managing real disasters and what can be learned from it. This paper reviews the Aceh Earthquake and Tsunami disaster in 2004 and the Fukushima Nuclear Disaster in 2011, as case studies. Published and grey literatures relating to these events were searched from online sources. Two major mismatches between leadership theory and reality were noted: effective communication and ability to co-ordinate resources at all levels. To improve leadership in disaster management, mitigation measures, preparedness and skills in crisis communication must be top-notch, communication disruption must be overcomed as soon as possible; and all entities involved in disaster management must know their roles.